SAT0624 Quantitative 3D imaging of tenosynovitis and bone marrow edema by DCE-MRI is a sensitive measure of response to therapy in rheumatoid arthritis. (15th June 2017) - Roberts, C; Guillard, G; Bowes, MA; Burlison, J; Khan, A; Maguire, N; Gotla, S; Morgan, A; Parker, GJ; Hodgson, R; Freeston, J; Vital, EM; et al.
Abstract : Background: Quantitative analysis of tissue microvascular function using dynamic contrast-enhanced MRI (DCE-MRI) shows promise for improved understanding of synovial pathophysiology in rheumatoid arthritis (RA). Assessing tenosynovitis and bone marrow edema (BME) using physiologically-interpretable measures such as K trans may offer additional insights; this will require increased precision in quantification. Objectives: To apply a 3D DCE-MRI method to quantify capillary permeability ( K trans ) in tendons, bone marrow edema, and to explore muscle involvement. To generate precise and consistent 3D regions of interest (ROI) of tenosynovitis and BME using active appearance models (AAMs)? and evaluate response to therapy within these regions. Methods: MR images of the hand were acquired in 27 patients with established RA who had recently commenced the same biological therapy. Subjects were imaged at 0, 3, 6 months. The MRI protocol included pre- and post-contrast high-resolution 3D FLASH acquisitions. The DCE-MRI scan protocol included T1 mapping sequences followed by 15 sequential volumes acquired over 5 minutes, during which a bolus of gadolinium (0.1 mmol/kg) was administered at 2 ml/s at the beginning of the 5th volume measurement. The Extended Kety model was applied to each voxel concentration-time series within ROIs, allowing voxelwise estimates of K trans . Pre-contrast T1-weighted mages were searched using 3D active appearance models (AAMs) to reliably identify tendons and their sheath in the carpal tunnel region as well as bones and marrow area. Images from the dynamic series were registered to the high-resolution pre-contrast images, providing standardised 3D ROIs for each of the regions. Median K trans was summarised in each patient for each ROI. T-test (p<0.05) determined significant differences from baseline. Results: Differences in baseline K trans were observed in each tissue type and demonstrated that highest levels of inflammation within the synovium, followed by tenosynovitis, BME and detection of low grade inflammation in the muscle (Fig. 1 ). Significant post-therapy responses in K trans, indicating a reduction in perfusion and capillary permeability associated with reduced inflammation, were seen in each of these tissue types (Fig.1 ). RAMRIS scoring showed no significant change at either 3 or 6 months. 3D visualisation of K trans in tenosynovitis revealed additional spatial response to the biological treatment (Fig. 2) – most of the remaining tenosynovitis at 6 months had lower permeability with almost all of the higher permeability class of synovitis disappearing after therapy. Conclusions: 3D DCE-MRI measures of tenosynovitis and bone marrow edema are practical in RA MR imaging trials, and offer sensitivity to change and differential tissue response not visible with other methods. Therapy-induced response in muscle suggests that there may be an inflammatory process in RA affecting local muscle groups. Disclosure of Interest: None declared